Rancang Bangun Web Pengaduan Masalah Sampah dan Edukasi Berbasis Gamifikasi Struktural - Septiana, Yosep; Kilin, Mochammad Agus Dharma (Jurnal Algoritma, 2025)
The waste problem in Indonesia, particularly in urban areas, remains a complex and persistent environmental issue. Garut Regency faces serious challenges in waste management, with an average daily production of around 230 tons, of which only 30 percent can be managed optimally. Low public awareness and limited participation in reporting waste-related issues remain major obstacles to effective handling. This study designs and develops a web-based waste complaint and education platform incorporating structural gamification as an effort to increase community engagement. The system design applies the Rational Unified Process (RUP), which involves four phases: Inception, Elaboration, Construction, and Transition. The application was built using the Laravel framework and MySQL as its database, featuring location-based reporting, follow-up management by officers, and environmental education supported by structural gamification elements such as points, levels, badges, and rewards. Testing results show a user satisfaction rate of 90.45 percent in the “strongly agree” category, indicating that the system operates well and meets user needs. Beyond serving as a reporting tool, the system also functions as an educational platform that enhances motivation and community involvement through the application of structural gamification elements for sustainable waste management.